Jeffrey Parker: Global Crisis: War, Climate Change and Catastrophe in the Seventeenth Century - Dalby, Andrew (Petits Propos Culinaires, 2013)
Jeffrey Parker: Global Crisis: War, Climate Change and Catastrophe in the Seventeenth Century: Yale University Press, 2013: 874 pp., illustrations, hardback, £29.99.